1999
DOI: 10.1021/ie980636n
|View full text |Cite
|
Sign up to set email alerts
|

Improved Regulatory Control of Industrial Gas-Phase Ethylene Polymerization Reactors

Abstract: This paper investigates the application of two techniques to improve the proportional-integral (PI) control performance when implemented to stabilize the operation of gas-phase polyethylene reactors around an optimal operating point which is open-loop unstable. The first technique deals with improving the performance of a single input-single output control loop through employing an on-line adaptive tuning strategy. The purpose of the tuning strategy is to force the closed-loop response to fit inside a desired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The authors found that a multi-loop control scheme must be used to improve the feedback response and they did so using an NLMPC controller. The authors, in another study, tried to overcome the PI shortcomings in SISO and MIMO cases by on-line adaptive tuning and finding proper control structures (Ali and Abasaeed 1999). Ghasem (2000) also studied the dynamics of a UNIPOL ® process using their model a PI controller.…”
Section: Conventional Controlmentioning
confidence: 99%
“…The authors found that a multi-loop control scheme must be used to improve the feedback response and they did so using an NLMPC controller. The authors, in another study, tried to overcome the PI shortcomings in SISO and MIMO cases by on-line adaptive tuning and finding proper control structures (Ali and Abasaeed 1999). Ghasem (2000) also studied the dynamics of a UNIPOL ® process using their model a PI controller.…”
Section: Conventional Controlmentioning
confidence: 99%
“…Dadebo et al 2 controlled the temperature and showed that the nonlinear error trajectory controller (ETC) displayed better performance when compared with an optimally tuned proportional-integral-differential (PID) controller and that nonlinear controllers have an advantage as they are more capable of rejecting disturbances and ensuring stability. Ali et al 14 have tried to control monomer concentration and reactor temperature using improved single-input/single-output (SISO) and multi-input/multi-output (MIMO) PI-based controllers by manipulating the catalyst feed rate, U 0 /U mf ratio and feed temperature. Sato et al 15 designed a model inverse optimal MIMO servo controller with integral actions plus an attached nonlinear compensator to control MFI and polymer density by altering the fresh hydrogen and butene feed concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Stabilization of polyethylene reactors is therefore a challenging problem and needs to be addressed through good control. Dadebo et al 5 and Ali et al 6,7 have addressed the stabilization of the reactor temperature through different approaches. Recently, Seki et al 8 have also studied the stabilization of gas-phase polyethylene reactors through an adequate tuning of the proportionalintegral-derivative controller.…”
Section: Introductionmentioning
confidence: 99%